The association of risk factors with psychiatric symptoms and quality of life in laryngopharyngeal reflux disease patients - Ramadhani, Ade; Dewi, Anna M. K.; Yunika, Kanthi; Budiarti, Rery; Ruspita, Dian A.; ., Farokah; ., Muyassaroh (International Journal of Research in Medical Sciences, 2020)
Background: Risk factors for laryngopharyngeal reflux (LPR), such as age, gender, BMI, smoking history and dietary habit affect the severity of LPR. These risk factors have a clinical impact on both social and emotional aspects, which can reduce the quality of life. Thus led the researchers to analyse association between these risk factors with psychiatric symptoms and quality of life for LPR sufferers. Methods: Analytical descriptive research with cross-sectional approach to LPR patients in ENT clinic RSUP Dr. Kariadi Semarang. Sixty six samples aged 18-60 years and met the criteria of the researcher were measured using the DASS 21 questionnaire and the RQS questionnaire. Statistical analysis used the chi-square test. Results: Obtained 66 subjects with a mean age of 45.1 years, there were more women than men (75.8%). Analysis of risk factors associated with depression found gender (p=1.000), age (p=1.000), duration of symptoms (p=1.000), BMI (p=0.132), smoking (p=0.452), and diet (p=1.000). Analysis of risk factors with anxiety obtained gender (p=0.340), age (p=0.743), duration of symptoms (p=0.085), BMI (p=0.322), smoking history (p=1.000), and diet (p=1.000). Analysis of risk factors with stress obtained gender (p=0.798), age (p=0.088), duration of symptoms (p=0.324), BMI (p=0.276), smoking history (p=0.606) and diet (p=0.538). Analysis of the gender association related to the quality of life LPR patients (p=0.032). Conclusions: Duration of symptoms, age, BMI, smoking history and diet were not associated with psychiatric symptoms and quality of life in LPR sufferers. Gender is not associated with psychiatric symptoms but is related to quality of life.